2020
DOI: 10.1088/1755-1315/616/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Farmer’s Knowledge in Land Suitability Evaluation and Farmers’ Awareness in Organic Farming for Sustainable Agriculture: A Case Study in Perlis

Abstract: Sustainable agriculture is the heart of organic farming, and human resources are playing a vital role in directing the community toward sustainable development in agricultural practices. The research objective is to evaluate the Farmer’s Knowledge (FK) in land suitability variables for crop type’s suitability in Perlis. After that, the collected spatial information variables applied to allocate the spatial distribution for four main crop types in Perlis. Besides that, to investigate farmer’s awareness in organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Organic matter in the soil functions to improve the physical properties of the soil, improve chemical properties and improve soil microbiology (Abdullah et al, 2020). A high organic material content will make land processing easier, because the soil structure becomes more crumbly, the growth of microorganisms is better, and root growth is more optimal.…”
Section: Fig 1 Map Of Actual Land Suitability For Dragon Fruit Plants...mentioning
confidence: 99%
“…Organic matter in the soil functions to improve the physical properties of the soil, improve chemical properties and improve soil microbiology (Abdullah et al, 2020). A high organic material content will make land processing easier, because the soil structure becomes more crumbly, the growth of microorganisms is better, and root growth is more optimal.…”
Section: Fig 1 Map Of Actual Land Suitability For Dragon Fruit Plants...mentioning
confidence: 99%
“…The theory that guides the operation of AHP helps to integrate different criteria in the hierarchy of their importance [53]. As such, existing literature revealed that many researchers (Abdullah et al [54], Antwi et al [55], Pachemska et al [56]) have employed AHP for different consistent land evaluation purposes. On the other hand, the literature also has other multicriteria methods that could be employed for land evaluation among which are Artificial Neural networks [32]; simple additive scoring (Aldababseh et al [31], Alilou et al [34]), and Linear combination and developing fuzzy-logic as reported by Balogun et al [25].…”
Section: Data Requirement For Spatial Analysismentioning
confidence: 99%